Digital Humanities as Inclusive Knowledge Translation: a Multi-Phase Qualitative Pilot Study - John C H. Hu (International Journal of Qualitative Research, 2023)
Knowledge translation (KT), the dissemination of research outputs towards utilization and application, is increasingly recognized in research. For marginalized populations, benefiting from research outputs can be hindered by longstanding, inequitable access to information and education. The objective of this pilot study is to assess the potential of using creative works in the digital humanities - such as films, series, animations, games, and graphic novels - as knowledge translation tools for engagement, inclusivity, and equitable access to research-based knowledge. Methods followed a multi-phase process. First, an exploratory literature review was conducted on the intersection between three pillars: digital humanities, marginalized populations, and knowledge translation (Web of Science and Scopus), with 21 studies that met the inclusion criteria. Operational definitions and project framework (CATER) were drawn from the gap analysis, followed by a first round of pilot interviews with individuals with qualitative research experience. The first pilot interviews were conducted to identify any conceptualization errors and address methodological concerns. The second round of pilot interviews was conducted with marginalized individuals. Research findings show that marginalized populations access digital humanities for self-motivated learning. The implications of this research suggest digital humanities can serve as KT tools to supplement existing modes of KT, and that further participatory research will help uncover complex relationships between digital humanities and living with marginalization.